PENERAPAN MODEL DISCOVERY LEARNING BERBASIS PERMAINAN ULAR TANGGA UNTUK MENINGKATKAN HASIL BELAJAR DAM MOTIVASI BELAJAR SISWA PADA MATERI IPA TENTANG UNSUR, SENYAWA DAN CAMPURAN PADA KELAS VIII MTsN 2 KOTA BLITAR - Aulia, Maulidatul; Samasta, Nadia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This Classroom Action Research (CAR) aims to determine the systematic steps for implementing a discovery learning model based on the snakes and ladders game to improve the motivation and learning outcomes of eighth-grade students at MTsN 2 Kota Blitar on the topic of elements, compounds, and mixtures. The study was conducted over two cycles, with two meetings in each cycle. The systematic steps of the discovery learning model include stimulation, problem identification, data collection, data processing, verification, and generalization. The results of the study indicate that the implementation of the discovery learning model successfully improved students’ motivation and learning outcomes on the topic of elements, compounds, and mixtures. In Cycle I, learning motivation increased from 57.5% (fair category) to 77.5% (good category) in Cycle II. Furthermore, the percentage of students who achieved mastery learning improved from 48% in Cycle I to 76% in Cycle II.